Rethinking neutrality: a conceptual analysis. Issue 1 (March 2021) - Watson, Matt
Abstract : This article attempts to determine whether there exists a coherent, plausible, and ultimately compelling explication of what it is to act neutrally. I argue that there is – an account I label neutrality of volition, and according to which an actor acts non-neutrally where she either acts for the purpose of differentially helping or hindering a particular party in a given contest, or acts or in the belief that there is a substantial likelihood that her action will have this effect. Along the way, I suggest that political philosophers concerned with whether justice requires that the state's laws and policies be publicly justifiable, as well as legal commentators who note that oftentimes laws of general application have disparate impacts, would do well to cease framing their arguments in the language of neutrality. I conclude by arguing that debate over the proper interpretation of neutrality is not merely a matter of semantics. Having identified an account of neutrality that aligns with our ordinary understanding of the concept, and which is also internally consistent, we have access to a conceptual tool that we can use to make better sense of a wide array of actions in the political sphere and beyond, while also avoiding an unhelpful conflation of neutrality with distinct concepts such as fairness, public justifiability, anti-perfectionism, equal impact, and non-discrimination.